2016
DOI: 10.1017/s0016756816000686
|View full text |Cite
|
Sign up to set email alerts
|

Alluvial fan, braided river and shallow-marine turbidity current deposits in the Port Lazo and Roche Jagu formations, Northern Brittany: relationships to andesite emplacements and implications for age of the Plourivo-Plouézec Group

Abstract: Facies and stratigraphic analysis of the Port Lazo and Roche Jagu formations, together the lower part of the Plourivo-Plouézec Group, suggests deposition in three distinct depositional systems. The lower part of the Port Lazo Formation comprises red conglomerate, sandstone and shale of alluvial fan to alluvial plain origin. A conformable interval of grey sandstone and shale succeeds the lower Port Lazo red beds and records a period of subtidal sedimentation dominated by river-fed, shallow-water turbidity curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…Marine incursions into the fluvial strata resulted in deposition of the Bluestone Bay Sandstone Member of the Alderney Sandstone Formation in the northern basin and the Erquy Quartzite Member and the Port Lazo Formation Upper Member in the southern basin (Went, , ).…”
Section: Geological Setting and Previous Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Marine incursions into the fluvial strata resulted in deposition of the Bluestone Bay Sandstone Member of the Alderney Sandstone Formation in the northern basin and the Erquy Quartzite Member and the Port Lazo Formation Upper Member in the southern basin (Went, , ).…”
Section: Geological Setting and Previous Workmentioning
confidence: 99%
“…They are finer grained than the repetitively stacked sheets of trough cross‐stratified sandstone that underlie and pre‐date them. The Roche Jagu Formation is fine to medium‐grained with localized very fine sandstone and mudstone beds (Went, ).…”
Section: Fluvial Deposits Of the Series Rougementioning
confidence: 99%
See 2 more Smart Citations
“…Flume experiments showed that increasing vegetation coverage can be related to restrained braiding and development of planform sinuosity (Gran & Paola, ; Tal & Paola, ). However, all of this evidence has been challenged on several fronts, owing to: (i) non‐unique solutions regarding whether vegetation promoted fluvial sinuosity in the early Palaeozoic or the opposite (Santos et al ., ; and ensuing debate in Davies et al ., ; and Santos et al ., ); (ii) the ever‐increasing documentation of pre‐vegetation alluvial strata that demonstrates a remarkable similarity in planform style (Santos et al ., ; Ielpi & Rainbird, , ; Santos & Owen, ; Went, ; Ghinassi & Ielpi, ; Ielpi, ; Ielpi et al ., ; Went & McMahon, ), channel geometry (Ielpi et al ., , ) and discharge regimes (Long, , , ; Nicholson, ; Ielpi & Ghinassi, ; Ielpi & Rainbird, ) with post‐vegetation rivers; (iii) alternative flume experiments where meander bends are maintained in the absence of vegetation (Peakall et al ., ), or where vegetation itself promotes flow disturbance, channel branching and eventual bar braiding (Coulthard, ); and (iv) the direct observation of modern, vegetation‐devoid fluvial landscapes capable of maintaining aggradational meandering channels (Li & Bristow, ; Li et al ., ; Ielpi, , ). In its broader sense, this debate represents a fundamental trial of uniformitarianism between modern and pre‐Silurian sedimentary landscapes, and could eventually disclose – or rule out – parallels between fluvial systems on Earth and other planetary bodies (e.g.…”
Section: Introductionmentioning
confidence: 99%